1987
DOI: 10.1161/01.str.18.4.733
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural characteristics of occluded perforating arteries in stroke-prone spontaneously hypertensive rats.

Abstract: We studied ultrastructurally cerebral perforating arteries in 60 stroke-prone spontaneously hypertensive rats (SHRSP), which were sequentially killed at 4-52 weeks of age before showing symptoms of stroke. Another 24 SHRSP were killed soon after they showed symptoms of cerebral infarction. The initial vascular lesions observed in the asymptomatic group included focal cytoplasmic necrosis in the outer layers of the media. This change progressed to widespread medial necrosis with time. In the infarction group, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 29 publications
2
60
1
Order By: Relevance
“…Therefore, in animals fed a salt-loaded diet, tissue infarctions occur in 80% of 30-week-old male SHRSP (Yamori and Horie, 1977;Tagami et al, 1987). On the contrary, the average onset for corresponding symptoms in SHRSP fed a standard diet without supplemental salt is 9 months (male rats) and 1.2 years (female rats) (Henning et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in animals fed a salt-loaded diet, tissue infarctions occur in 80% of 30-week-old male SHRSP (Yamori and Horie, 1977;Tagami et al, 1987). On the contrary, the average onset for corresponding symptoms in SHRSP fed a standard diet without supplemental salt is 9 months (male rats) and 1.2 years (female rats) (Henning et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…collagen), wall thickening and luminal narrowing, local BBB leakage, and perivascular oedema (Ogata et al, 1981;Fredriksson et al, 1985Fredriksson et al, , 1988aTagami et al, 1987). These vessel changes were especially evident in aged individuals (Hart et al, 1980;Ogata et al, 1981;Tagami et al, 1987). Vessel changes resembling SVD were also seen in R + /A + transgenic mice (Baumbach et al, 2003;Iida et al, 2005;Wakisaka et al, 2008) and in peripheral vascular beds of IHR rats (Kantachuvesiri et al, 2001), though reported data are sparse.…”
Section: Models That Resemble Svd Arterial Vasculopathymentioning
confidence: 99%
“…One model, the spontaneously hypertensive stroke prone rat develops arteriolar wall thickening, subcortical lesions, enlarged perivascular spaces, and cortical infarcts and hemorrhages, which are exacerbated with hypertension. [12][13][14][15] Blood-brain barrier breakdown, evident by the leakage of immunoglobulin G and dextran, as well as the aggregation of platelets in the vicinity of vascular stases has also been observed. 16,17 Furthermore, ultrastructural changes to astrocytic endfeet in the spontaneously hypertensive stroke prone rat model are indicative of changes in the gliovasculature.…”
Section: Introductionmentioning
confidence: 99%